1984
DOI: 10.1172/jci111532
|View full text |Cite
|
Sign up to set email alerts
|

New mutants of apolipoprotein E associated with atherosclerotic diseases but not to type III hyperlipoproteinemia.

Abstract: Abstract. We analyzed the heterogeneity of apo E in very low density lipoprotein from 58 hyperlipidemic subjects with or without atherosclerosis, 69 patients with ischemic heart disease, and 100 apparently healthy individuals. Apo E gene frequencies in the group of healthy individuals were comparable with those in German and American populations. The distribution of six common apo E phenotypes in the groups of hyperlipidemia and ischemic heart disease was similar to that in the healthy group.In addition to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
1

Year Published

1985
1985
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(23 citation statements)
references
References 33 publications
1
21
1
Order By: Relevance
“…Apo E5 and apo E7 have been detected in about 5~ of Japanese patients with hyperlipidemia and ischemic heart disease, while they were not found among 100 healthy Japanese (Yamamura et al, 1984a;Yamamura et al, 1984b). We also found four cases with apo E5 or apo E7 (4.3%) out of 92 patients with myocardial infarction (Hamaguchi et al, in preparation).…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Apo E5 and apo E7 have been detected in about 5~ of Japanese patients with hyperlipidemia and ischemic heart disease, while they were not found among 100 healthy Japanese (Yamamura et al, 1984a;Yamamura et al, 1984b). We also found four cases with apo E5 or apo E7 (4.3%) out of 92 patients with myocardial infarction (Hamaguchi et al, in preparation).…”
Section: Discussionmentioning
confidence: 58%
“…We also found four cases with apo E5 or apo E7 (4.3%) out of 92 patients with myocardial infarction (Hamaguchi et al, in preparation). Yamamura et al (1984b) observed that five of seven patients with apo E5 or apo E7 had overt atherosclerotic disease.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations